(untitled) (Bulletin KNOB, 1992)
The restoration of the former deanery, the house of the ’propositus’ of Saint Lebuinus’s chapter and church in Deventer, resulted in an interim report of the building-historical and archaeological investigations. This Romanesque building erected around 1130 (dendrochronological date) functioned as a gate of the immunity of the church, situated along the Carolingian border of the settlement. The gate lost its function in the course of the enlargement of the town during the late 12th century. Within the medieval town plan the gate and the house played a central part. The old core of the building consists of thick, massive walls of natural stone imported from the Rhine area, such as: tufa, trachyte and a kind of limestone from the interior of Roman aqueducts. Not only the building materials, but also the architectural forms, including the five Romanesque windows, point to a German influence at that time. In the middle of the 13th century the vaulted rooms of the gate were extended with two vaulted bays, later on with a third, and functioned as a chapel until the Reformation. The archaeological excavations gave information on the early phases of the building, older activities on this spot, a wooden structure, ceramics (of the type of Dorestad W IVa) and glass down to the late 9th century. Very rare in this case was the complete stratification of the soil from the 9th century to the 12th century.